2019
DOI: 10.3390/f11010027
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Forest Management Practice in Nepal: Critical Reflections from Stakeholders’ Perspectives

Abstract: Design and application of context-specific forest management practices with the participation of key stakeholders plays a significant role in sustainable forest management outcomes. However, key forestry stakeholders often hold different, and sometimes conflicting, expectations in relation to forest management policies and management objectives. Applying the triple-perspective typology of stakeholder theory, this paper assessed the evolution of “Scientific Forest Management” (SciFM), a signature programme of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…Effectiveness of any forest management practices relies on complexities or adoption and the cost or profit made (Poudyal et al 2019). However, this study acknowledged some of the limitations as (1) cost regarding managing the matured natural forest might be underestimating and less in concluding the profitability studies as associated indirect cost and cost of raising the matured forest is missing (2) associated indirect benefits (monetary value) in managing the forest (natural regeneration/health of forest) were not computed (3) potential productivities based on climatic data were not compared with periodic measurement of similar types of managed forest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectiveness of any forest management practices relies on complexities or adoption and the cost or profit made (Poudyal et al 2019). However, this study acknowledged some of the limitations as (1) cost regarding managing the matured natural forest might be underestimating and less in concluding the profitability studies as associated indirect cost and cost of raising the matured forest is missing (2) associated indirect benefits (monetary value) in managing the forest (natural regeneration/health of forest) were not computed (3) potential productivities based on climatic data were not compared with periodic measurement of similar types of managed forest.…”
Section: Discussionmentioning
confidence: 99%
“…This follows primarily the Irregular Shelterwood Silvicultural System with very high-intensity logging, leaving behind 15-30 mature mother trees per hectare (DoF 2014). The vision of the government outlined as "Forestry for Prosperity" laid the policy foundation for SciFM as one of the four key pillars of prosperity (Poudel 2018;Poudyal et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The vision thus laid the foundation for scientific forest management (SciFM) and for sustainable management in Production forests.Later on, governmentalso developed and enacted the Scientific Management Guidelines in 2014. The government has defined the SciFM as "an application of appropriate silviculture system and forest management principles through design of systematic compartment of fixed rotation age" (Poudyal et al, 2019). The Sustainable forest management was aimed to maintain and enhance the economic, social and environmental values of all types of forests, for the benefit of present and future generations (FAO, 2020).…”
Section: In-situ Conservationmentioning
confidence: 99%
“…The relationship between forest and community in Indonesia is supported by the existence of customary law (Marta et al 2019;Dasrizal et al 2019;Ifrani et al 2019) that provides the opportunity for the local community to manage forest areas (Mutolib et al 2020;Lestawi and Bunga 2020). Several studies have shown that the local community can perform proper and sustainable forest management (Handoko 2014;Matsvange et al 2016;Poudyal et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The government continues to reduce community activity around the forest. It can damage forest sustainability (Surati 2014; Purwawangsa 2017), even though several studies observed that the customary community could preserve the forest (Handoko 2014;Matsvange et al 2016;Poudyal et al 2019). Still, an in-depth study is necessary to examine facts regarding customary community and efforts to sustain forest area, whether the customary community can preserve the forest if they manage it themselves, and ensure that forest management by the local community will have an impact on forest sustainability.…”
Section: Introductionmentioning
confidence: 99%